Tribology of new thin compression ring of fired engine under controlled conditions-A combined experimental and numerical study. (December 2018) - Zavos, Anastasios; Nikolakopoulos, Pantelis G.
Abstract: In this paper, a CFD model combined with experimental measurements of the ring deformations, in a single-cylinder fired engine, using a strain gauge through the cylinder bore is presented. The strain gauge data is analysed to measure the primary reflection due to friction between the thin compression ring and the cylinder wall. The findings show that the prediction of the calculated ring friction, needs the suitable surface roughness, particularly at TDC reversal. The experiments under cold controlled condition and low engine speed, proved that a higher contribution is noticeable by thin compression ring friction. In addition, the investigation of lubricant film and flow rate is shown that the thin profile design can affect the sealing performance momentary of compression ring. Graphical abstract: Highlights: An extensive combined experimental and numerical investigation for frictional performance of a new thin compression ring at controlled conditions has been presented. The limitations in the design of the test rig have been introduced and discussed. A new thin compression ring has been measured and simulated to predict friction, lubricant film and lubricant flow rate. The influence of surface topography on friction has been introduced. The tribological performance of measured ring profile and artificial (parabolic) ring profile has been presented and compared.